1993
DOI: 10.1111/j.1526-4610.1993.hed33040210.x
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Patients Suffering from Temporo‐mandibular Disorders and a General Headache Population

Abstract: The purpose of this study was to examine the possible association of signs and symptoms of temporomandibular disorders relative to headache. Fifty-six sequential patients referred to the Headache Institute of Minnesota for evaluation and treatment of migraine and tension headaches were examined for signs and symptoms of temporomandibular disorders. The results of the examination of headache patients were compared to patients suffering from myofascial pain dysfunction and/or TMJ internal derangements from the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 6 publications
0
12
0
2
Order By: Relevance
“…Most studies show increased pericranial tenderness [10][11][12][13][14][15] and tenderness elsewhere in the body 16 only during migraine attacks, whereas other studies have reported that patients with migraine exhibit increased pericranial muscle tenderness even in the absence of a headache. [17][18][19][20] Nevertheless, the influence of MFP on PPT of masticatory muscles in migraineurs has not been investigated yet.…”
Section: Discussionmentioning
confidence: 96%
“…Most studies show increased pericranial tenderness [10][11][12][13][14][15] and tenderness elsewhere in the body 16 only during migraine attacks, whereas other studies have reported that patients with migraine exhibit increased pericranial muscle tenderness even in the absence of a headache. [17][18][19][20] Nevertheless, the influence of MFP on PPT of masticatory muscles in migraineurs has not been investigated yet.…”
Section: Discussionmentioning
confidence: 96%
“…Although the three branches innervate different regions of the face, there is evidence in inflammatory diseases that activation of one branch of the trigeminal nerve can cause activation of the other major branches leading to pathophysiological changes. For example, there is significant comorbidity reported for patients suffering from temporomandibular joint (TMJ) disorders (V 3 ) that also experience headache and migraine (V 1 ) 25,26 . In addition, during severe migraine attacks, patients often report facial pressure or pain and nasal congestion, which involve V 2 branches 14 .…”
Section: Commentsmentioning
confidence: 99%
“…The criteria did not include pain to palpation of these muscles since there was overlap between the TMJ ID/MPD subjects and general headache subjects for palpation pain in these muscles. 3 The fact that functional testing of these muscles elicited pain and discriminated between the groups is significant since functional testing is less subjective and less technique sensitive than muscle palpation. Tables 3 and 4, although the diagnostic criteria has acceptable sensitivity and specificity in differentiating general headache patients from MPD and TMJ ID patients, it is clear that false-positive and false-negatives are possible.…”
Section: Commentsmentioning
confidence: 99%